Gold rush societies and migrant networks in the Tasman world - Davy, Daniel (Associate professor of history) (Studies in British and Irish migration., 2021)
"This book creatively explores the gold rushes in the Tasman World through an examination of the Otago gold rushes, revealing how transnational connections and local social and natural environments shaped colonial identities. The first monograph-length study on the Otago gold rushes and their place in the histories of British and Irish migration, it increases our understanding of the British World by grounding transnational networks in the local ecologies, geologies and weather patterns which shaped local social structures and profoundly affected migrants' relationships to loved ones in Britain, Ireland and elsewhere."--